International Handbook of Information Technology in Primary and Secondary Education
DOI: 10.1007/978-0-387-73315-9_35
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Leadership and IT

Abstract: except for brief excerpts in connection with reviews or scholarly analysis. Use in connection with any form of information storage and retrieval, electronic adaptation, computer software, or by similar or dissimilar methodology now known or hereafter developed is forbidden. The use in this publication of trade names, trademarks, service marks, and similar terms, even if they are not identified as such, is not to be taken as an expression of opinion as to whether or not they are subject to proprietary rights.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
68
1
3

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(72 citation statements)
references
References 19 publications
0
68
1
3
Order By: Relevance
“…School administrators, teachers, students, parents, and other communities can all be the leaders. (Bennett, Wise, Woods & Harvey, 2003) Institutionalization: Distributed leadership includes all forms of collaboration and participation within the school. It is integrated into the school culture and daily routines.…”
Section: Distributed Leadershipmentioning
confidence: 99%
See 1 more Smart Citation
“…School administrators, teachers, students, parents, and other communities can all be the leaders. (Bennett, Wise, Woods & Harvey, 2003) Institutionalization: Distributed leadership includes all forms of collaboration and participation within the school. It is integrated into the school culture and daily routines.…”
Section: Distributed Leadershipmentioning
confidence: 99%
“…(Gronn, 2002) Fluidity: The boundaries between the leader and followers are blurred. Leadership does not reside in formal positions or specific roles, but emerges from the practice (Spillane, 2006;Bennett, et. al., 2003).…”
Section: Distributed Leadershipmentioning
confidence: 99%
“…Most advocates agree that distributed leadership is not the anti-thesis of top-down, hierarchical leadership (e.g., [52,[58][59][60]) but essentially involves the vertical and lateral dimensions of leadership practice, encompasses both formal and the informal forms. Bennett et al [58] noted that conceptions of distributed leadership often signal the openness of boundaries and describe its ability to encourage the development of networks rather than relying on traditional hierarchically structured decision-making and communication concept.…”
Section: Introductionmentioning
confidence: 99%
“…We found that despite the various claims of positive effects of distributed leadership practices, very few studies that acknowledge the different patterns of leadership distribution (e.g., [59,[78][79][80]) and fewer (e.g., [81,82]) that examined their relations with organizational outcomes. Furthermore, literature shows that the majority of texts produced on distributed leadership were based on examination in the context of school and educational improvement and rarely in community engagement settings (e.g., [49][50][51][52][53][54][55][56][57][58][59][60][61][62]65,67,68]).…”
mentioning
confidence: 99%
See 1 more Smart Citation